1978
DOI: 10.1084/jem.148.6.1449
|View full text |Cite
|
Sign up to set email alerts
|

Role of phagocytosis in the activation of macrophages

Abstract: Macrophages are found in large numbers at sites of chronic inflammation . They enter the lesions as monocytes (1) and develop in situ into large cells which synthesize and release an impressive variety of enzymes such as lysosomal hydrolases (2, 3), plasminogen activator (4), elastase (5), and collagenase (6) . These enzymes are most likely involved in the extensive destruction of cellular and extracellular tissue elements which accompanies chronic inflammation .Since macrophages are highly phagocytic, we have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0
1

Year Published

1979
1979
1997
1997

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(55 citation statements)
references
References 16 publications
2
52
0
1
Order By: Relevance
“…Phagocytosis is the main function of macrophages. It is also a powerful stimulus of macrophage activation (Schnyder & Baggiolini, 1978b) as shown by the greatly increased oxygen metabolism and hexose monophosphate shunt activity (Karnovsky, Lazdins & Simmons, 1975), release of products of arachidonic acid metabolism (Humes, Bonney, Dahlgren, Sadowski, Kuehl & Davis, 1977;Brune, Glatt, Kalin & Peskar, 1978), and induction of secretion of lysosomal hydrolases and neutral proteinases (Schnyder & Baggiolini, 1978b). Our data indicate that, in macrophages activated by phagocytosis, arachidonic acid is metabolised to a significant extent through the lipoxygenase pathway.…”
Section: Discussionmentioning
confidence: 74%
“…Phagocytosis is the main function of macrophages. It is also a powerful stimulus of macrophage activation (Schnyder & Baggiolini, 1978b) as shown by the greatly increased oxygen metabolism and hexose monophosphate shunt activity (Karnovsky, Lazdins & Simmons, 1975), release of products of arachidonic acid metabolism (Humes, Bonney, Dahlgren, Sadowski, Kuehl & Davis, 1977;Brune, Glatt, Kalin & Peskar, 1978), and induction of secretion of lysosomal hydrolases and neutral proteinases (Schnyder & Baggiolini, 1978b). Our data indicate that, in macrophages activated by phagocytosis, arachidonic acid is metabolised to a significant extent through the lipoxygenase pathway.…”
Section: Discussionmentioning
confidence: 74%
“…Schnyder and Baggiolini reported the inability of latex to cause "macrophage activation" (6). We showed that the ingestion of latex in a particle to cell ratio range of 5 to 40 did not significantly affect either factor B or other enzyme secretion.…”
Section: Discussionmentioning
confidence: 56%
“…On the other hand, the synthesis of intracellular lactic dehydrogenase by zymosan-ingesting macrophages did not show an initial suppressive response but increased without a lag. It is known that, when macrophages ingest particles such as zymosan, a large quantity of enzymes escapes from lysosomes fused with phagocytic vacuoles (6,7). Therefore, one possible explanation for the early suppression of factor B secretion is that the more zymosan particles the macrophage ingests, the less factor B and lysosomal enzymes are retained by the macrophages at the beginning of cultivation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations